Perbedaan Kadar Kolesterol Total Antara Penderita Stroke Iskemik dan Stroke Hemoragik di RSUD Dr. Moewardi - Aini, Athiefah Qurrotul (2016)
Background: Stroke is one of the world's problems that become the third leading cause of death in the world, after heart disease and cancer. Stroke in Indonesia caused the most of death, amounting to 15,4%. Lipid levels is one of the factors that affect short-term morbidity from stroke, so that the differences in the levels of lipids in the evaluation of stroke subtype is very important to do. Based on research conducted by Chaudhury (2014), there were differences in total cholesterol levels significantly between patients with ischemic stroke and hemorrhagic stroke, while according to Dey (2010) there was no difference in total cholesterol levels between patients with ischemic stroke and hemorrhagic stroke. Purpose: to determine whether there are differences in total cholesterol among patients with ischemic stroke and hemorrhagic stroke at Hospital Dr. Moewardi. Methods: The design of this research is analytic observational study with cross sectional approach. Data were retrieved from medical records of patients with ischemic stroke and hemorrhagic stroke that ever hospitalized at Hospital Dr. Moewardi years 2014-2015, who have met the inclusion and exclution criteria. Total sample size was 60 people, consisting of 30 patients with 30 patients with ischemic stroke and hemorrhagic stroke. The data were analyzed with the unpaired t test. Results: Data analysis by unpaired T test showed the results of p=0.005. Total cholesterol levels in patients with ischemic stroke had a mean of 202 ± 33.9 mg / dL, which is higher than the total cholesterol in patients with hemorrhagic stroke which had a mean 167.87 ± 53.6 mg / dL, with a difference of 33.4 mg / dL Conclusions: There are differences in total cholesterol levels among patients with ischemic stroke and hemorrhagic stroke. Total cholesterol levels in patients with ischemic stroke is higher than patients with hemorrhagic stroke